Capturing the HIV-related social exclusion practices experienced by key populations through photovoice: an interpretative phenomenological study - Ami Kamila; Widyawati Widyawati; Mubasysyir Hasanbasri; Mohammad Hakimi (BMC, 2024)
Abstract Background Key populations are defined as groups that are susceptible to HIV, including Men Sex with Men (MSM), Transgender (TG), Persons who Inject Drug (PID), and Female Sex Worker (FSW). These key populations groups are among the fastest-growing populations in Indonesia. These vulnerable groups are ostracized by society and health services, which makes it difficult to get treatment. This project was carried out to investigate the different experiences and perspectives of these key populations in facing and addressing social and spiritual exclusion. Methods A qualitative phenomenological study using photovoice was carried out from July to December 2022. Key populations comprising MSM, TG, PID, and FSW were recruited from community-based peer groups in West Bandung Regency using snowball sampling. This was followed by the Photovoice stages, from workshops to focus group discussions and interviews with audio recordings. Furthermore, thematic data analysis was carried out by interpretative participant narratives and photographs supported by Atlas.ti software. Result Eighteen participants comprising four MSM, five TG, four PIDs, and five FSWs participated in this research. Among these eighteen participants, six were HIV-negative, including 3 PIDs and 3 FSWs, while the remaining were positive. The analysis of the collected data identified four main themes: 1) limited access like unequal treatment, disadvantage, and harassment, 2) social and spiritual impact, 3) coping mechanisms, and 4) self-reflection through photovoice. These results showed that social exclusion occurred in an environment where community values, beliefs, and norms dehumanised these key populations, and where removal of support and care was prominent. Despite these challenges, participant resilience was evidenced by using internal resources and peer support as coping mechanisms. The participants considered photovoice as a tool to foster self-confidence and self-awareness through a reflective process. Conclusions The findings of this study highlight the emphasis on participants' openness in sharing their experiences, which can build empathy and promote a more inclusive community in HIV prevention efforts. This research findings can be used to inform HIV policy and practice and inclusion of these key populations in the community. We advocate making the photovoice efforts accessible to a wider audience through exhibitions and various media.